Analisis Isi Instagram @Lantassurabaya Dalam Penyampaian Informasi Kecelakaan Lalu Lintas - Naufal Labiib; Ahmad Aldiansyah; Wisnu Sartiko; Muhamad Ali Ro'is; Denny Oktavina Radianto (KOLONI, 2024)
Technology 4.0 has entered people's lives because of globalization, people's behavior can change with technology. As a social media, Instagram has a platform for disseminating news, one example is the @lantassurabaya account, which includes traffic accident information which is useful in providing important information about accidents. With Instagram media, although the @lantassurabaya account is relatively new, it is spreading quickly, this account is useful for people who drive, therefore the information on Instagram social media provides a positive side in disseminating traffic accident news. Content analysis method, content analysis is a research technique for interpreting text or content. content analysis technique whose aim is to explain and provide an overview of the delivery of information through the categorization contained in the content uploaded by @lantassurabaya on Instagram, content limits start from 17 – 21 November 2022 with consideration of uploads that contain elements of traffic accidents. The results of the research show that in every upload uploaded by @lantassurabaya it is always determined to provide information on the location of the accident, the aim is to make it easier for readers to know clearly, it can make it easier for parties related to the victim such as family and relatives to get information easily, which reflects the relationship with the delivery. information, how information can be easily received by audiences clearly